2013
DOI: 10.1002/jgrd.50772
|View full text |Cite
|
Sign up to set email alerts
|

Temperature trends in the tropical upper troposphere and lower stratosphere: Connections with sea surface temperatures and implications for water vapor and ozone

Abstract: [1] Satellite observations and chemistry-climate model experiments are used to understand the zonal structure of tropical lower stratospheric temperature, water vapor, and ozone trends. The warming in the tropical upper troposphere over the past 30 years is strongest near the Indo-Pacific warm pool, while the warming trend in the western and central Pacific is much weaker. In the lower stratosphere, these trends are reversed: the historical cooling trend is strongest over the Indo-Pacific warm pool and is weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
33
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 74 publications
12
33
0
2
Order By: Relevance
“…The evolution of cold point temperatures (defined in section 3) is overlaid on the water vapor evolution, and indicates that this drop in water vapor was due to a cooling of cold point temperatures. Hence, SST changes contributed to the drop (in agreement with Rosenlof and Reid, 2008), but were not the major forcing factor, consistent with Garfinkel et al (2013b) and Brinkop et al (2016). The rest of the drop is associated with the QBO and with BDC variability (Randel et al, 2006;Fueglistaler, 2012;15 Fueglistaler et al, 2014;Dessler et al, 2014).…”
Section: Composite Analysis Of the 97/98 Event As Compared To Other Esupporting
confidence: 53%
See 1 more Smart Citation
“…The evolution of cold point temperatures (defined in section 3) is overlaid on the water vapor evolution, and indicates that this drop in water vapor was due to a cooling of cold point temperatures. Hence, SST changes contributed to the drop (in agreement with Rosenlof and Reid, 2008), but were not the major forcing factor, consistent with Garfinkel et al (2013b) and Brinkop et al (2016). The rest of the drop is associated with the QBO and with BDC variability (Randel et al, 2006;Fueglistaler, 2012;15 Fueglistaler et al, 2014;Dessler et al, 2014).…”
Section: Composite Analysis Of the 97/98 Event As Compared To Other Esupporting
confidence: 53%
“…Hence, an ENSO event that more efficiently warms the mid-troposphere (such as the 1997/1998 event) can more efficiently moisten the stratosphere. It has been suggested that SST changes in the Indo-Pacific contributed to some of the post-2000 drop in water vapor (Rosenlof and Reid, 2008;Garfinkel et al, 2013b) via ENSO (Brinkop et al, 2016), and here we consider whether the AGCM simulations simulate 8 Atmos. Chem.…”
Section: Composite Analysis Of the 97/98 Event As Compared To Other Ementioning
confidence: 99%
“…The increase in wtrue¯* extends well above the level at which the diabatic heating ends, consistent with Holloway and Neelin [] and Garfinkel et al . [].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that El Niño events intensify the vertical propagation of ultra-long Rossby waves in the Northern Hemisphere during winter and thereby strengthen the BDC (Rao J et al, 2019a). This effect has been seen in observational records (Van Loon and Labitzke, 1987;Labitzke and Van Loon, 1989;Camp and Tung, 2007;Garfinkel and Hartmann, 2007;Free and Seidel, 2009) and has been reproduced in modeling studies (Hamilton, 1993;Sassi et al, 2004;García-Herrera et al, 2006;Manzini et al, 2006;Taguchi and Hartmann, 2006;Xie F et al, 2012;Garfinkel et al, 2013b;Rao J and Ren RC, 2016Rao J et al, 2019a, b, c). Therefore, we focused on the planetary wave activity during ENSO events that peak in the winter and decay in the spring.…”
Section: Mechanisms Of Seasonal Variation In Enso Effects On the Watementioning
confidence: 73%